FoxP3+ CD8 T-cells in acute HIV infection and following early antiretroviral therapy initiation - Yero, Alexis; Shi, Tao; Routy, Jean-Pierre; Tremblay, Cécile; Durand, Madeleine; Costiniuk, Cecilia T.; Jenabian, Mohammad-Ali (Frontiers in Immunology, 2022)
Objectives: Besides CD4 regulatory T-cells (Tregs), immunosuppressor FoxP3+ CD8 T-cells are emerging as an important subset of Tregs, which contribute to immune dysfunction and disease progression in HIV infection. However, FoxP3+ CD8 T-cell dynamics in acute HIV infection and following early antiretroviral therapy (ART) initiation remain understudied. Methods: Subsets of FoxP3+ CD8 T-cells were characterized both prospectively and cross-sectionally in PBMCs from untreated acute (n=26) and chronic (n=10) HIV-infected individuals, early ART-treated in acute infection (n=10, median of ART initiation: 5.5 months post-infection), ART-treated in chronic infection (n=10), elite controllers (n=18), and HIV-uninfected controls (n=21). Results: Acute and chronic infection were associated with increased total , effector memory, and terminally differentiated FoxP3+ CD8 T-cells, while early ART normalized only the frequencies of total and terminally differentiated FoxP3+ CD8 T-cells. We observed an increase in FoxP3+ CD8 T-cell immune activation (HLADR+/CD38+), senescence (CD57+/CD28-), and PD-1 expression during acute and chronic infection, which were not normalized by early ART. FoxP3+ CD8 T-cells in untreated participants expressed higher levels of immunosuppressive LAP(TGF-β1) and CD39 than uninfected controls, whereas early ART did not affect their expression. The expression of gut-homing markers CCR9 and Integrin-β7 by total FoxP3+ CD8 T-cells and CD39+ and LAP(TGF-β1)+ FoxP3+ CD8 T-cells increased in untreated individuals and remained higher than in uninfected controls despite early ART. Elite controllers share most of the FoxP3+ CD8 T-cell characteristics in uninfected individuals. Conclusions: Although early ART normalized total FoxP3+ CD8 T-cells frequencies, it did not affect the persistent elevation of the gut-homing potential of CD39+ and LAP(TGF-β1)+ FoxP3+ CD8 T-cell, which may contribute to immune dysfunction.